The traumatic aspect of naming: Psychoanalysis and the Freirean subject of (class) antagonism - Armonda, Alex J. (Educational philosophy and theory, 2024)
Deploying a Lacanian conceptual framework, this article interrogates the psychoanalytic underpinnings of Paulo Freire's dialogical method of critical pedagogy. The paper advances the claim that the transformative efficacy of Freirean dialogue is rooted in its unique ability to confront and engage the repressed element of trauma, or what Lacan calls the real. The author suggests that the locus of trauma stands as the elusive, yet central and constitutive axis around which Freire's dialogical engagement turns. Following psychoanalysis' attention to biography, the paper first examines how Freire's personal experience of exile informs his philosophical orientation to being, politics, and education. Turning to a specific classroom event Freire outlines in Pedagogy of Hope, the paper then develops a new interpretation of Freire's idea of naming, and through Lacanian analysis, extends Freire's insight on the relationship between psyche, ideology, and social antagonism. Pushing the idea of class subjectivity in Freire beyond its familiar determinants (namely as an 'identity'), the paper resituates the notion of radical subjectivity in critical pedagogy as the effect of a traumatic loss or gap in the sociosymbolic order of being. The author argues that the 'naming event' in Freire is formally rooted in an encounter with this unconscious gap. To conclude, the paper offers critical educators some new points of departure for conceptualizing the transformative labor of problem-posing dialogue.